Adaptive Strategies for MSME Sustainability in Infrastructure-Affected Zones: A SWOT–SEM Analysis in Perbaungan, Indonesia: English - Anshar; Lubis, Satia Negara; Sabrina, T (CV. ARGA FARMA, 2025)
Major infrastructure developments, such as toll road construction, can significantly alter local economic dynamics by shifting accessibility patterns and consumer mobility. This study explores the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Pasar Bengkel, Perbaungan District, North Sumatra, following the diversion of traffic due to the Medan–Tebing Tinggi toll road segment of the Trans-Sumatra Highway. Employing an integrated quantitative–strategic approach, the research combines Structural Equation Modeling (SEM) with SWOT analysis to assess the effects of transportation infrastructure (X1), government policy (X2), and adaptive capacity (X3) on MSME sustainability (Y). The SEM results demonstrate that adaptive capacity exerts the most substantial influence on sustainability (β = 0.784, p < 0.001), followed by government policy support (β = 0.330, p = 0.007), whereas transportation infrastructure presents a non-significant effect (β = 0.136, p = 0.202). The structural model explains 68.7% of the variance in MSME sustainability (R² = 0.687). Complementing this, SWOT analysis places MSMEs in Quadrant II (WO strategy), reflecting high external opportunities—such as digital transformation, e-commerce access, and rest area integration—paired with internal challenges, including limited digital skills and disrupted foot traffic. These findings underscore the pivotal role of firm-level adaptability and targeted policy mechanisms in fostering resilience. The study contributes to the discourse on place-based regional planning by proposing actionable, evidence-based strategies that align infrastructure interventions with inclusive, sustainable local economic development.